Formation and time dynamics of hydrogen-induced vacancies in nickel. (15th October 2021) - Chiari, Luca; Kojima, Kenji; Endo, Yusuke; Teshigahara, Hiroki; Butterling, Maik; Liedke, Maciej Oskar; Hirschmann, Eric; Attallah, Ahmed G.; Wagner, Andeas; Fujinami, Masanori
Abstract: The formation of hydrogen-induced defects in nickel was investigated by positron annihilation lifetime spectroscopy (PALS) and the time dynamics of those defects during room temperature aging was tracked with an unprecedented time resolution of the order of minutes using an ultrahigh-flux slow positron beam. Those measurements showed the formation of a large number of atomic vacancies simply by hydrogen addition at room temperature. Low-temperature PALS measurements indicated that they were monovacancy-level defects and low-temperature coincidence Doppler broadening measurements proved that hydrogen was trapped and bound to those vacancies during the hydrogen charge. Room temperature aging, i.e. below the stage III temperature in Ni, and the concomitant hydrogen desorption induced the agglomeration of those monovacancies into large vacancy clusters which remained even after all the hydrogen had desorbed and hydrides had disappeared. These results constitute the first empirical evidence that vacancy-hydrogen complexes are induced in Ni only by hydrogen charging and demonstrate that hydrogen has a primary role in the formation and stabilization of vacancies even at room temperature. Graphical abstract: Image, graphical abstract